Factors influencing consumers’ intention to use self-ordering kiosk in restaurant - Yong, Jian (2022)
The objective of this research project is to determine the factors that influence the consumers’ intention to use the self-ordering kiosk in restaurant such as perceived usefulness, perceived ease of use, perceived enjoyment, and trust. Researcher has started off by identifying all the problem statements and research objectives, following by explaining and discussing each independent variables and dependent variable in literature review before proceeding with the research methodology. A total of 320 of questionnaires had been distributed and answered by the respondents through online, and data from 314 qualified respondents had been collected and examined by using Statistical Package for Social Science (SPSS) 26.0 to conduct analyzation and construction of graphs and tables for analysis purposes. The outcomes that obtained from this study proved that all independent variables (perceived usefulness, perceived ease of use, perceived enjoyment, and trust) have the relationship towards intention to use self-ordering kiosk in restaurant. Furthermore, theoretical implications and practical implications have been explained and suggested for the academicians who may wanted to refer this research to support their study, and for business owners or other related practitioners as a reference for them to improve based on the findings and results that obtained from this research project. Lastly, limitations of this research projects have listed out and recommendations have provided for the future researchers who interested in related field.